PRODUCT ATTRIBUTES AND NORMS ROLES IN FORMING INTENTIONS TO BUY COUNTERFEIT PRODUCTS - Rolan Mart Sasongko (JWM (JURNAL WAWASAN MANAJEMEN), 2017)
Buying counterfeit products is a habit and a common thing that causes some problems, especially in the country that has not developed yet, one of them is Indonesia. The counterfeiting activities undoubtedly harmed the original producers, both local producers and international producers because counterfeit products have the advantage of product attributes compared to the original product. The objective of this study is to examine the influence of product attributes consisting of price, quality, and convenience to purchase intention of counterfeit products, also the role of subjective norms as a moderating variable. The sample consists of 200 respondents who have intentions to buy counterfeit “Nike” shoe in Surakarta is collected by the method of purposive sampling. Multiple Group Structural Equation Modeling analysis is used to explain the variables that hypothesized. The results of the study showed that the intentions to buy counterfeit products significantly influenced by the price, quality, and convenience in getting the product. Then, subjective norms variable moderate the relationship between both quality and convenience with intention to buy counterfeit product, but not moderate the influence of the price. The conclusion in this research is the price is the main factor that motivates consumer to buy counterfeit product.